Stress Tests By The European Banking Authority: The Immunity Of Italian Cooperative Banks - Quintiliani, Andrea (Journal of Applied Business Research, 2017)
Purpose. The objectives of the paper are two-fold. The first objective of the research is formulated with the intent to analyze the existence or not of a possible “European Banking Authority (EBA) effect” on the credit offer of local banks compared with national banks subject to the requests of capital from European Authority. The second research objective aims to understand what are the conditions that allow to develop a model of a local bank capable of supporting SMEs, with a suitable risk-return profile. Methodology. This paper presents an empirical comparative analysis between Cooperative Credit Banks (BCCs) and Italian banking groups. Findings. The empirical analysis shows how the financial then real crisis has not induced BCCs to restrict credit to firms. In particular, the BCCs not included in stress exercises, show, unlike national banks, a substantial “independence” of credit trend from the advices of the Authority. The survey evidences have however highlighted some critical elements that are reflected inevitably on the local bank’s risk-return profile. Research Limitations. The quantitative nature of the empirical analysis must be followed by a qualitative analysis in order to strengthen the validity of the results. Implications. This work will be useful to stimulate the debate on the studies of local banks and their anti-cyclic role in favor of the SMEs. Originality. The work affects an aspect which has hitherto been little studied.